Mechanism(s) for age-related sex differences in diet-induced cardiomyopathy: role of RNA methylation. (3rd October 2022) - Croft, A; Kelly, C; Chen, D; Murtha, L; Sugito, S; Boyle, A; Sverdlov, A L; Ngo, D T M
Abstract: Background/Introduction: Age and sexual dimorphism contribute to the differential cardiometabolic dysfunctions associated with diet-induced obesity. However, the underlying mechanisms remain elusive. RNA modifications via RNA m6A methylation, is an emerging mediator of RNA stability, translation and localization responsible for regulation of multiple biological functions. RNA m6A modifications are regulated by "writers", "erasers" and "readers". The role of RNA methylation machinery genes in the heart is largely unexplored, and may provide insight into the influence of age and sex on cardiometabolic dysfunction. Purpose: We aim to determine differential RNA methylation changes within the heart in a diet-induced cardiomyopathy mouse model, stratified according to age and sex. Methods: Male and female C57BL/6 mice (6–8wk-old) were fed normal chow (NC) or high-fat/high-sucrose (HFHS) diet for 1 or 4 months. Echocardiographic measurements were performed at 1 and 4 months according to the American Society of Echocardiography and European Association of Cardiovascular Imaging guidelines. At study endpoint, glucose and insulin tolerance testing was conducted by injecting mice intraperitoneally with 2g/kg glucose or 0.6U/kg insulin, and monitoring blood glucose levels over a 2 hour period. RNA from heart tissue was subjected to quantitative PCR for RNA methylation machinery genes (FTO, ALKBH5, METTL3, METTL4, METTL14, YTHDF1 and YTHDF2). PPIA was used to normalise qPCR data. Results: Both male and female mice showed evidence of age- and diet-induced metabolic dysfunction, however, males and females showed markedly different metabolic impairments. For example, glucose tolerance was exacerbated by 4 months of HFHS diet in males but not females; and only females showed impaired insulin tolerance. Echocardiography showed that males had systolic (stoke volume, cardiac output) and diastolic (E/A ratio) dysfunction after 4 months of HFHS diet, while females were unperturbed. We identified that METTL3 and METTL14, the "writers" of m6A methylation, were consistently increased in male mouse hearts at 1 vs 4 months of age but were unchanged or decreased in females, irrespective of diet. Conversely, YTHDF1, a "reader", was unchanged in male mouse hearts at 1 vs. 4 months of age but was significantly increased in female hearts. Conclusion: Our study confirms that markedly different cardiometabolic impairments occur in male versus female mice in response to long-term HFHS diet. Despite significant metabolic impairment in both sexes, cardiac dysfunction was only evident in males. RNA methylation machinery genes were differentially expressed in mouse hearts according to age and sex, suggesting that RNA methylation may be involved in age-related sexual dimorphism in cardiometabolic impairments. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Heart Foundation